Mechanical model for complex brackets system of the Taiwanese traditional Dieh-Dou timber structures. Issue 1 (January 2016) - Yeo, Sok-Yee; Komatsu, Kohei; Hsu, Min-Fu; Que, Zeli
A static test was conducted to investigate the elastic and post-yielding structural behaviour of complex brackets system along the corridor frame region of the Taiwanese Dieh-Dou timber structures. One partial fully scaled specimen was loaded horizontally under different vertical loading levels. A mechanical model, focusing mainly on the rotational behaviours of bearing blocks and timber interlocking joints, was developed to estimate the global behaviour of complex brackets of the Dieh-Dou corridor frame region. By assuming each spring stiffness to behave bi-linearly, the model is only valid for the estimation of the primary and secondary stiffnesses. The force–deformation relationship is highly dependent on the rotational spring stiffness and vertical loads. Hence, when a heavier vertical load is imposed onto the structure, yielding rotation increases and subsequently, the yielding moment of the bearing block members is improved further. Generally, the predicted model was in good agreement with the observed results, up to the post-yielding loading level.